Dinâmica mutacional e epigenética do genoma de candida albicans durante evolução in vitro sob hipóxia e choque térmico - Bartelli, Thais Fernanda [UNIFESP] (2016)
The commensal fungus Candida albicans colonizes several niches in the human body and is part of the microbiota of healthy individuals. It is also an opportunistic pathogen and causative agent of superficial and systemic infections in immunocompromised hosts, with a high mortality rate. To effectively colonize or infect a host, these fungi must adapt to physical constraints in the human body, such as its low oxygen tension (hypoxia, 5%CO2), and temperature (37°C heat shock). Previous studies have demonstrated that the genetic variability of C. albicans isolates is an important adaptive mechanism, although little is known about the effect of environmental conditions on their mitochondrial genomes. To simulate the physical environmental factors affecting C. albicans, two strains, SC5314 and L757, were subjected to an in vitro evolution scheme under hypoxia and 37°C for up to 48 weeks in order to evaluate the synergistic effect of oxygen tension and temperature on C. albicans mitochondrial genome (mtDNA). Sequencing of mitochondrial fragments over different periods (6, 12, 24 and 48 weeks) of strain SC5314 or sequencing the complete mitochondrial genome of both strains after 12 weeks grown in non-fermentative medium (GTH12) showed no sequence variation and/or lesions in mtDNA sequences, which kept their integrity even after 48 weeks. Under these different conditions, the mtDNA copy number mean values were invariant (nonsignificant differences in mean and variance). On the other hand, sequencing of nuclear gene fragments of strain SC5314 showed loss of heterozygosity after 48 weeks, on samples cultured in normoxia (normal oxygen tension) and 28°C (GVN48) and at 37 °C and hypoxia (DTH48). In addition, sequencing of the complete nuclear genome of strain SC5314 GTH12, revealed microvariations as compared to the same strain before in vitro evolution, with at least 155 variable alleles involved with regulatory processes and pathogenicity (adhesion and hyphal growth), including 19 involved in mitochondrial functions. Although we have not identified sequence changes in the mtDNA during in vitro evolution, we have described, for the first time, the whole mitochondrial genome methylation map of C. albicans. Our results indicate that environmental conditions, such as continuous exposure to hypoxia and 37°C affect the methylation patterns in a strain-specific manner, therefore providing a clue on how C. albicans employs epigenetic mechanisms for its survival in mammalian hosts.